Elaboration and sensory evaluation of added cookie from jackfruit seed and vegan dulce de leche (Research, Society and Development, 2020)
Oilseed milk more specifically from Brazil nuts is a food of high nutritional value that can be used as a raw material for various preparations or be consumed in natura as a substitute for animal milk, making it a viable option for intolerants lactose, or individuals who have veganism as their lifestyle. The use of vegetable milk and the insertion of flours such as jackfruit seed as a substitute for cocoa has been studied, promoting the use of the seed and the insertion of nutrients in the preparations. Given the above, the objective was to develop formulations of cookies added with sweet milk from Brazil nuts and jackfruit flour, as well as assessing their sensory characteristics. To this end, two formulations of cookies were prepared, vegan dulce de leche and evaluated for sensory characteristics through affective testing using a structured hedonic scale of nine points. As a result, it was observed that the scores attributed by the tasters in the sensory analysis of cookies varied between 6.9 - 7.9, for the evaluated attributes, being situated between the hedonic terms I liked slightly and I liked moderately, respectively. For the purchase intention the notes are between 4.2 and 4.3 referring to the possibly buy on the hedonic scale. Thus, it is concluded that the vegan cookie has satisfactory sensory characteristics and obtained good sensory acceptability, with the jackfruit flour and the Brazil nut milk ingredients in promising in the bakery industry.